Utilization of Hemicelluloses as Example for Holistic Recovery of Agricultural Residues - Jahn, Annika; Thummler, Katrin; Gebke, Stefan; Kahl, Martin; Aubel, Ines; Fischer, Steffen; Bertau, Martin (Chemie Ingenieur Technik, 2020)
The objective of this work was to separate and characterize the hemicellulose from agricultural residues of annual plants and to achieve a suitable application for it. Therefore, different treatments for producing pulp were tested and compared. Wheat straw and oat husks were digested by alkaline pulping and delignification. Pectin from sugar beet pulp was obtained by acid extraction. Beside the production of pulp, the separation and utilization of hemicellulose as resource was a key aspect of this work. The hemicelluloses were tested as paper additives, flame retardants and flotation agents.
Created from Fastlane, Scopus look-up
Keywords: Agricultural residue; Flame retardants; Flotation agent; Hemicellulose; Paper additive